The essence of nursing a patient with chronic heart failure – case study - Tkaczyk, Filip M. (Nursing Problems / Problemy Pielęgniarstwa, 2023)
Chronic heart failure is associated with the disturbance of the physiological activity of the heart muscle, and it directly contributes to the occurrence of specific clinical symptoms such as shortness of breath, oedema, and deterioration of physical exercise tolerance. The aim of this work is to present the essence of nursing a patient with chronic heart failure, hospitalized due to exacerbation of the symptoms of the disease. A 77-year-old patient was admitted to the Cardiology Department in an emergency due to the progression of decompensated heart failure. On admission, the patient was diagnosed with circulatory and respiratory disorders. After 10 days of hospitalization, the patient’s general condition improved, and the patient was qualified for ICD implantation. Heart failure manifests numerous clinical symptoms. An important task of interdisciplinary teams is health education, focused on self-control and self-care.